The Role of Nurses on the Psychosocial Quality of Type 1 Diabetes Mellitus Patients in a Hospital in Lombok, Indonesia - Nasirin, Chairun (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes mellitus is a chronic condition characterized by increased concentrations of blood glucose, or high blood sugar, accompanied by the emergence of a typical main symptom of urine that tastes sweet in large amounts. The World Health Organization confirmed that diabetes mellitus is one of the 10 main diseases, causing 382 million deaths. The role of nurses is significant in maintaining the quality of life of patients and providing psychosocial support to patients with diabetes mellitus. The purpose of this study was to determine the role of nurses in the psychosocial quality of life of type 1 diabetes mellitus patients at a hospital in East Lombok, Indonesia. The population in this study were all type 1 diabetes mellitus clients, totaling 100 people at the hospital, with the sample in this study being 70 respondents using total sampling techniques. By using analysis of data using the Spearman rank test, the results of this study indicate that there is a relationship between the role of nurses and the psychosocial quality of life of type 1 diabetes mellitus patients at the hospital. As evidenced by the results of the Spearman rank test with the value of p-value < α (0.00 < 0.05), this study confirmed that there is a relationship between the role of nurses and the psychosocial quality of life of type 1 diabetes mellitus patients.